Entitas Hidup dan Relasi Teologis Material dalam Tradisi Petik Pari: Kajian Neo-Materialisme - Ayu Sefiana; Sony Sukmawan (JENTERA: Jurnal Kajian Sastra, 2025)
This study aims to analyze the meaning of living entities and material theological relations in the tradition of rice harvesting through the perspective of neo-materialism, particularly regarding rice, offerings, and rituals that reflect the Javanese people's views on life and spirituality. A descriptive qualitative approach focused on agricultural ethnography was used to study the tradition practiced in Harjokuncaran Village, Sumbermanjing Wetan District, Malang Regency, from March to June 2025. Data collection included participatory observation, semi-structured interviews with farmers who practice the tradition, and documentation. Data analysis used the Miles and Huberman model within a neo-materialist framework that emphasizes material agency in the context of Javanese agrarian culture. The results of the study show that rice functions as an active actor that has sensitivity and will, manifested through the concepts of pari lanang and pari wadon in the kemantenan ritual. Mbok Sri Kuning acts as a protective spiritual entity that mediates material-immaterial relationships, while offerings, mantras with figurative language (metaphors, antithesis, repetition, pleonasm), and Javanese calendar calculations form a material theological relationship that integrates physical and spiritual dimensions. These findings reveal the concept of distributed agency in Javanese agrarian traditions, namely that the materiality of rice and ritual elements are not merely passive symbols but active actors that form spiritual networks and create cosmic harmony. This research contributes to expanding the understanding of material agency (thing power) in the study of Javanese literature and agrarian rituals, proving that material objects have the capacity to shape cultural and spiritual meanings independently. Abstrak Penelitian ini bertujuan menganalisis makna entitas hidup dan relasi teologis material dalam tradisi petik pari melalui perspektif neo-materialisme, khususnya mengenai padi, sesajen, dan ritual mencerminkan pandangan masyarakat Jawa tentang kehidupan dan spiritualitas. Pendekatan kualitatif deskriptif yang berfokus pada etnografi pertanian digunakan untuk mengkaji tradisi yang dilakukan di Desa Harjokuncaran, Kecamatan Sumbermanjing Wetan, Kabupaten Malang pada periode Maret hingga Juni 2025. Pengumpulan data meliputi observasi partisipatif, wawancara semi-terstruktur dengan petani pelaksana tradisi, dan dokumentasi. Analisis data menggunakan model Miles dan Huberman dalam kerangka neo-materialisme yang menekankan agensi material pada konteks budaya agraris Jawa. Hasil penelitian menunjukkan padi berfungsi sebagai aktor aktif yang memiliki kepekaan dan kehendak, diwujudkan melalui konsep pari lanang dan pari wadon dalam ritual kemantenan. Mbok Sri Kuning berperan sebagai entitas spiritual pelindung yang memediasi hubungan material-immaterial, sementara sesajen, mantra dengan struktur majas (metafora, antitesis, repetisi, pleonasme), dan perhitungan hari Jawa membentuk relasi teologis material yang mengintegrasikan dimensi fisik dan spiritual. Temuan ini mengungkapkan konsep distributed agency dalam tradisi agraris Jawa, bahwasanya materialitas padi dan elemen ritual bukan sekadar simbol pasif melainkan aktor yang aktif membentuk jaringan relasi spiritual dan menciptakan harmoni kosmik. Kontribusi penelitian ini memperluas pemahaman agensi material (thing power) dalam kajian sastra dan ritual agraris Jawa, membuktikan bahwa objek-objek material memiliki kapasitas untuk membentuk makna budaya dan spiritual secara independen.